HERPES ZOSTER OPHTHALMICUS: CLINICAL SPECTRUM - Nowak, Magdalena Natalia; Wiśniewski, Konrad Oskar; Kuśmierowska, Natalia Sara; Polak, Milena B.; Karolak, Dominika; Słomkowski, Grzegorz; Kuś, Monika; Białowąs, Tymoteusz; Cholewiński, Kacper; Valipur Kolti, Daria (International Journal of Innovative Technologies in Social Science, 2026)
Objective: Herpes zoster ophthalmicus (HZO) is a severe manifestation of varicella-zoster virus reactivation affecting the ophthalmic branch of the trigeminal nerve. The aim of this review is to present the clinical spectrum of HZO and emphasize the importance of early diagnosis and treatment.Methods: A narrative review of the literature concerning epidemiology, pathophysiology, and ocular manifestations of HZO was conducted. Published clinical studies and reviews describing ocular complications and therapeutic strategies were analyzed.Results: HZO may involve multiple ocular structures, including eyelids, conjunctiva, cornea, uveal tract, sclera, retina, and optic nerve. The most common manifestations include blepharoconjunctivitis and keratitis, while severe complications may include uveitis, scleritis, acute retinal necrosis, optic neuritis, and cranial nerve palsies. Early antiviral therapy significantly reduces the risk of ocular complications and chronic disease.Conclusions: Herpes zoster ophthalmicus presents with a broad spectrum of clinical manifestations that may lead to permanent visual impairment if untreated. Early recognition, prompt antiviral therapy, and appropriate ophthalmologic management are essential for improving patient outcomes. Preventive vaccination plays an important role in reducing the incidence of the disease.